Correlation between Assertive Teaching Styles of Physics Teachers and Learning Outcomes of High School Physics Students - Khaeruddin, Khaeruddin; Nursarita, Nursarita; Palloan, Pariabti (Jurnal Pendidikan MIPA, 2022)
This research is ex-post facto research that aims to determine the correlation between assertive physics teachers' teaching style and physics learning achievements of high school students in Kabupaten Soppeng. The population in this research were students of XI MIPA in SMA Negeri in Soppeng, while the samples based on Proportional Random Sampling technique was 269 students. The research instrument was Teaching Style questionnaire and archive documentation of students' grades recap. Validation of the instrument using Gregory validity test, empirical validation and reliability test. The results showed the physics teacher used assertive teaching style with 85.50% while the student learning achievements were in high category with average of 86. From the analysis product moment correlation test results, the rcount value was 0.276 which was greater than the r table, 0.138 at a significance level of 5% thus the conclusion was assertive teaching style of physics teachers affects students' physics learning achievements. Keywords: teaching style, assertive teaching style, learning outcomes DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp968-983